2000
DOI: 10.1093/ptj/80.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Shoulder Kinematics and Associated Muscle Activity in People With Symptoms of Shoulder Impingement

Abstract: Background and Purpose. Treatment of patients with impingement symptoms commonly includes exercises intended to restore "normal" movement patterns. Evidence that indicates the existence of abnormal patterns in people with shoulder pain is limited. The purpose of this investigation was to analyze glenohumeral and scapulothoracic kinematics and associated scapulothoracic muscle activity in a group of subjects with symptoms of shoulder impingement relative to a group of subjects without symptoms of shoulder impin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
764
3
42

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 1,351 publications
(871 citation statements)
references
References 52 publications
25
764
3
42
Order By: Relevance
“…Research has shown that one-side sports such as volleyball causes accommodative changes in muscle strength within the dominant side [26]. The strength of the upper trapezius muscle of the dominant side in volleyball athletes was more than that in futsal athletes, which was in accordance with the findings of Ludewig [8]. In volleyball players, during the cocking and acceleration phases, the upper trapezius and serratus anterior play a significant role throughout the course of throwing movements that places the scapula in an elevation and upper rotation position [27].…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Research has shown that one-side sports such as volleyball causes accommodative changes in muscle strength within the dominant side [26]. The strength of the upper trapezius muscle of the dominant side in volleyball athletes was more than that in futsal athletes, which was in accordance with the findings of Ludewig [8]. In volleyball players, during the cocking and acceleration phases, the upper trapezius and serratus anterior play a significant role throughout the course of throwing movements that places the scapula in an elevation and upper rotation position [27].…”
Section: Discussionsupporting
confidence: 85%
“…Muscle weakness and muscle imbalance can cause impingement of the shoulder joint syndrome, therefore, evaluation of the ratio of antagonist-agonist of the scapulothoracic muscle on one side can help diagnose and treat [2,8,[22][23][24]. To measure the elevation to depression ratio of the scapula, the upper trapezius muscle was considered for elevation and the lower trapezius for depression [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, aspects of the transport component such as activation related to the scapular movement (i.e. an essential component for arm elevation) 22 may be affected, even in less severely impaired children. Furthermore, for children with moderate HCP, the impairment clearly impinges on proximal as well as distal transport components.…”
Section: Discussionmentioning
confidence: 99%
“…Critical to the movement of the scapula are the trapezius and serratus anterior muscles, both considered important in normal kinematics of the scapula (Ebaugh et al, 2005). Dysfunction of these muscles is thought to be related to shoulder pathology with evidence of differences in the activation patterns between subjects with shoulder pain and those who do not complain of shoulder symptoms (Cools et al, 2002;Lin et al, 2005;Ludewig & Cook, 2000). Clinically, scapular muscle function can be assessed by observing the position of the scapula, palpating scapular position and visualizing scapular changes during dynamic movement (Kibler & Sciascia, 2010;Mottram, 1997;Myers et al, 2005;Tate et al, 2008).…”
Section: Introductionmentioning
confidence: 99%